A SYSTEMATIC LITERATURE REVIEW: EXPLORING VARIABLES AND CONTEXTUAL APPLICATIONS OF THE USES & GRATIFICATIONS THEORY FRAMEWORK IN DIGITAL MEDIA PLATFORMS - Haryadi, Adi; Listyorini; Jennifer; Celina; Elsadi; Defriansyah (GoAcademica Research dan Publishing, 2025)
This study aims to conduct a comprehensive Systematic Literature Review (SLR) to explore the development and application of the Uses and Gratifications Theory (UGT) in the context of digital media. The review systematically examines literature published in English and indexed in the Scopus database between 2019 and 2024. Following the PRISMA framework, an initial pool of 1,899 articles was screened and refined to 48 empirical studies that met the inclusion criteria: empirical research focused on digital media and UGT, English-language publications, and genuine data aggregation using quantitative or qualitative methods. The synthesis reveals that the most dominant independent variables include media type, platform affordances, and user motivation, while the main dependent variables are engagement, satisfaction, and continued media use. The most recurrent uses and gratifications dimensions identified across studies are information seeking, entertainment, social interaction, personal identity, and escapism. These findings confirm that UGT continues to provide a robust theoretical framework for understanding user behavior in the digital era, especially concerning social media, online video platforms, and mobile applications. Through a syllogistic reasoning approach, the study concludes that digital media users actively construct their own media experiences based on personalized gratifications. However, research gaps remain in areas such as algorithmic influence on user motivation, cross-platform behavioral comparison, and the integration of emotional gratifications in AI-driven media environments. Overall, this review highlights the enduring relevance of UGT and its strategic implications for digital content design, user engagement, and media innovation.